Operando detection of single nanoparticle activity dynamics inside a model pore catalyst material - Albinsson, David (Sci Adv, 2020)
Nanoconfinement in porous catalysts may induce reactant concentration gradients inside the pores due to local conversion. This leads to inefficient active material use since parts of the catalyst may be trapped in an inactive state. Experimentally, these effects remain unstudied due to material complexity and required high spatial resolution. Here, we have nanofabricated quasi–two-dimensional mimics of porous catalysts, which combine the traits of nanofluidics with single particle plasmonics and online mass spectrometry readout. Enabled by single particle resolution at operando conditions during CO oxidation over a Cu model catalyst, we directly visualize reactant concentration gradient formation due to conversion on single Cu nanoparticles inside the “model pore” and how it dynamically controls oxidation state—and, thus, activity—of particles downstream. Our results provide a general framework for single particle catalysis in the gas phase and highlight the importance of single particle approaches for the understanding of complex catalyst materials.